On the Dynamics of an Eco-Epidemiological System Incorporating a Vertically Transmitted Infectious Disease - Abdul Satar, Huda; Ibrahim, Hiba Abdullah; Bahlool, Dahlia Khaled (Iraqi Journal of Science, 2021)
An eco-epidemiological system incorporating a vertically transmitted infectious disease is proposed and investigated. Micheal-Mentence type of harvesting is utilized to study the harvesting effort imposed on the predator. All the properties of the solution of the system are discussed. The dynamical behaviour of the system, involving local stability, global stability, and local bifurcation, is investigated. The work is finalized with the numerical simulation to observe the global behaviour of the solution.